Modified BARC Model Dryer Compared with Machanical Dryer and Conventional Sun Drying Based on Extent of Nutrient Loss in Dried Fish Products - Shiv Chandra Verma (School of Aquatic Food Products and Technology,CoF, 2016)
Abstract- The main objective of the study was to compare the extent of nutritional loss in seafood caused by drying in a modified BARC model solar dryer with that in an electrical (mechanical) dryer and that by direct drying under sun on a platform. Two products were prepared for the study, viz. dry salted threadfin bream (Nemipterus japonicus) and dried shrimp (Metapenaeus dobsoni).Rate of drying of salted fish or peeled shrimp was highest in electrical dryer, followed by that in solar dryer and was lowest on platform as indicated by the rate of decrease in moisture content and hence, decrease in water activity of the products.